PEMISAHAN PROTEIN DALAM DARAH PENDERITA DIABETES MELLITUS TIPE 2 UNTUK PENGEMBANGAN MOLEKUL BIOMARKER - Dewi Riskha Nurmalasari (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2021)
Diabetes mellitus (DM) is a disorder of the chronic metabolic system due to insufficiency of insulin function. DM is classified into two main categories, type 1 and type 2. The purpose of this study was to separate proteins using the SDS-PAGE method to determine the potential protein profile as a biomarker contained in the blood of type 2 DM patients, so that the results of the analysis can be used as an indicator of early detection of type 2 DM. This research is a true experimental research. The samples of this study were the blood of 20 patients with type 2 DM in Sukorejo Bangsalsari Village and the blood of 5 patients who non  DM in Sukorejo Bangsalsari Village. sampling technique was randomized controlled trial, after the blood collection process, blood serum was then prepared at the Molecular Biology Laboratory, FMIPA UNEJ, then protein analysis was performed using the 1D-gel electrophoresis (SDS-PAGE) method. The results of protein characterization using SDS-PAGE analysis with blood serum of type 2 DM patients and serum of healthy people (non-patients) as negative controls, obtained protein bands that are less specific to potential targets, because the results of running are still not good, so it is not possible to know the biomarker protein profile in the blood of patients with type 2 DM in Sukorejo Bangsalsari Village, and the results of this analysis still cannot be used as an indicator for early detection of type 2 diabetes mellitus. Analysis of potential proteins profile as biomarkers using SDS-PAGE analysis has revealed three bands which had molecular weights of 28, 45 and 235 kDa. Keywords: Diabetes mellitus, Biomarker, SDS-PAGE